Separation, purification, and crystallization of 1,5-pentanediamine hydrochloride from fermentation broth by cation resin - Li, Hui; Chen, Xu; Tang, Yibo; Yang, Yue; He, Feng; Wang, Xin; Li, Ganlu; Chen, Kequan; Ouyang, Pingkai; Yang, Yuning (Frontiers in Bioengineering and Biotechnology, 2023)
1,5-Pentanediamine hydrochloride (PDAH) was an important raw material for the preparation of bio-based pentamethylene diisocyanate (PDI). PDI has shown excellent properties in the application of adhesives and thermosetting polyurethane. In this study, PDAH was recovered from 1,5-pentanediamine (PDA) fermentation broth using a cation exchange resin and purified by crystallization. On the basis of static adsorption/desorption tests, D152 was selected as the most suitable resin for purifying PDAH. The effects of solution pH, initial temperature, concentration of PDA, and adsorption time were studied by the static adsorption method. The equilibrium adsorption data were well fitted to Langmiur, Freundlich, and Temkin-Pyzhev adsorption isotherms. The adsorption free energy, enthalpy, and entropy were calculated. The experimental data were well described by the pseudo first-order kinetics model. The dynamic experiment in the fixed bed column showed that under optimal conditions, the adsorption capacity reached 96.45 mg/g, and the recovery proportion of the effective section reached 80.16%. In addition, the crystallization of the PDAH solution obtained by elution proved that the crystal product quality of resin eluting solution was highest. Thus, our strategy for the separation and purification of PDAH from fermentation broth will contribute to the industrial scale-up of the separation of PDAH.